International Marketing Plan: Launch of Realeyes’ Services in Australia - Bettadapura Keshavamurthy, Sharath Kumar; Hsieh, Heng-Hui; Katti, Aditya (2009)
MBA Students of the Nottingham University Business School have been asked by Realeyes to device a marketing plan in order to internationalize their data services by launching their business in Australia. This has been undertaken as our MBA group management project. The following report is a product of extensive research of the Australian market for usability services in general and eye-tracking services in particular. We have employed both qualitative and quantitative research methods. Ethnographic research and in-depth interviews mainly comprise our qualitative research, where we have endeavoured to gain deep insights on segmentation and favourable segments, eye-tracking awareness in Australia, the B2B purchasing behaviour, the need for eye-tracking and usability-testing, and the perceived value of eye-tracking in Australia. The findings of this research have fed into our multi-perspective analyses. We have used our MBA toolkit, contemporary international marketing literature available that we have included in our Literature Review chapters, as well as industry methods to conduct our analyses of the firm’s capability and intent to internationalize, its industry, the factors of international business, and finally the Australian market-attractiveness analyses. The outcomes of our analyses are then used for designing suitable entry-mode strategy, targeting and positioning of Realeyes in Australia. Branding of an SME like Realeyes is analyzed thoroughly while evaluating the importance and means of communicating its brand in Australia. As part of Marketing Mix, the 7 P’s (Booms and Bitner, 1981) are rigorously discussed, with an emphasis on Pricing and International price strategic decision-making points that have been researched and recommendations suggested to Realeyes. Risks and barriers are analyzed and assessed. As an outcome, recommendations to avoid/tackle risk are made. As part of implementation and control, costs are measured against benefits to enter Australian markets, and an optimal break-even point is arrived at. The budget can be found in the appendices. The report is concluded by emphasizing the importance of Web-usability, digital adverts and software (desktop-usability) as a segment whilst paying attention to attractive segments like Outdoor Media and TV adverts.